2009
DOI: 10.1016/j.coi.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Follicular helper T cells as cognate regulators of B cell immunity

Abstract: SUMMARY Follicular helper T (TFH) cells are a class of helper T cells specialized in the cognate control of antigen-specific B cell immunity. Upon first contact with antigen-primed B cells, pre-germinal center effector TFH cells promote B cell clonal expansion, antibody isotype switch, plasma cell differentiation and the induction of germinal centers. In contrast, within germinal centers, TFH cells regulate the fate of antigen-specific GC B cells expressing high-affinity variant B cell receptors to promote mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 57 publications
4
133
0
Order By: Relevance
“…Within the same series of studies, IL-21R-deficient mice were also reported to have activation of a normal memory B cell response; however, quantitative analysis to support this assertion was not provided (17 (12,23). Alternatively, IL-21 may affect the differentiation program of B cells during the primary response or the quality of T cell help available, both of which could indirectly impact the characteristics of memory B cell response (41,42). Future studies will aim to determine the mechanism by which IL-21 augments the memory B cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Within the same series of studies, IL-21R-deficient mice were also reported to have activation of a normal memory B cell response; however, quantitative analysis to support this assertion was not provided (17 (12,23). Alternatively, IL-21 may affect the differentiation program of B cells during the primary response or the quality of T cell help available, both of which could indirectly impact the characteristics of memory B cell response (41,42). Future studies will aim to determine the mechanism by which IL-21 augments the memory B cell response.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility for uncontrolled B-cell activation in MyD88 À/À mice after RASV infection is failure in the feedback regulation of Tfh-cell generation and function by plasma cells. Recently, plasma cells were reported to regulate Tfh cells in an antigen-specific manner and mice deficient in plasma cells showed lack of negative feedback regulation for Tfh-cell activity [41,42]. Collectively, systemic hyper-IgG Ab response to persistent bacterial exposure might be initiated as a danger signal to provoke immune responses but fail to control the infection due to the lack of proper defense by the MyD88 molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The GC reaction is constrained by B-cell-extrinsic factors, including the size of the T FH population and Ag availability (16,17). B cells bearing high-affinity BCR out-compete lower affinity clones for access to T cell-mediated survival signals (18).…”
Section: Np-specific H2-o −/− B Cells Preferentially Populate the Gc mentioning
confidence: 99%
“…Therefore, rather than further study T-cell responses to the presentation of individual peptides, we measured the ability of GC B cells to obtain T-cell help from the pool of endogenous polyclonal CD4 + T cells. This sensitive and physiological approach allows the detection of overall differences in the efficiency of presentation of a polyvalent Ag by WT versus H2-O −/− B cells.The GC reaction is constrained by B-cell-extrinsic factors, including the size of the T FH population and Ag availability (16,17). B cells bearing high-affinity BCR out-compete lower affinity clones for access to T cell-mediated survival signals (18).…”
mentioning
confidence: 99%